'That b**** ruined my walk': FEMEN, Fashion Week and female spectacle. (1st May 2016) - Dungay, Leah
In September 2013, two topless female protesters arrived at Paris Fashion Week, found a way into the Nina Ricci Spring/Summer '14 show and abruptly joined the models on the catwalk. These women faced countless photographers, video cameras and journalists before being taken away by security. This article will critically analyse this action by the contemporary feminist protest group FEMEN, focusing on their use of 'female spectacle' and the group's complex relationship with the mass media and 'spectacular culture'. This article will consider the ways in which practises of risk, stunting and female spectacle are employed by FEMEN within their topless protest form in order to undermine the dominant hegemonic constructions of female identity. Thus, it will also examine criticisms surrounding FEMEN's problematic use of the gendered/sexualised female body in protest. This article will explore the content and focus of the subsequent media representation of the Fashion Week protest in order to examine FEMEN's belief in representational visibility as a form of political power.